2020
DOI: 10.1063/5.0015044
|View full text |Cite
|
Sign up to set email alerts
|

On respiratory droplets and face masks

Abstract: Face mask filters—textile, surgical, or respiratory—are widely used in an effort to limit the spread of airborne viral infections. Our understanding of the droplet dynamics around a face mask filter, including the droplet containment and leakage from and passing through the cover, is incomplete. We present a fluid dynamics study of the transmission of respiratory droplets through and around a face mask filter. By employing multiphase computational fluid dynamics in a fully coupled Eulerian–Lagrangian framework… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
276
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(284 citation statements)
references
References 39 publications
7
276
0
1
Order By: Relevance
“…The COVID-19 pandemic has necessitated universal face mask protocols for infection control, which has resulted in significant interest in understanding face mask effectiveness from various disciplines, 11 , 15 , 16 , 17 including ophthalmology 18 . However, there are few data on how patient face mask use may alter bacterial dispersion during an intravitreal injection, which subsequently may affect the risk of post-injection endophthalmitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID-19 pandemic has necessitated universal face mask protocols for infection control, which has resulted in significant interest in understanding face mask effectiveness from various disciplines, 11 , 15 , 16 , 17 including ophthalmology 18 . However, there are few data on how patient face mask use may alter bacterial dispersion during an intravitreal injection, which subsequently may affect the risk of post-injection endophthalmitis.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the tight-fitting face without tape may result in a greater amount of bacterial dispersion upward toward the subject’s eye. 12 , 17 Indeed, a recent study assessing respiratory droplet velocities with face mask use during simulated coughs reported that even with tight-fitting face masks, small openings can lead to leakage of droplets around the mask. 17 However, our study suggests that securing the superior portion of the same, tight-fitting face mask with adhesive tape significantly decreased the amount of bacterial growth, suggesting that securing the superior portion of the mask with tape may create an important barrier for upward bacterial dispersion.…”
Section: Discussionmentioning
confidence: 99%
“…Wilkes etc. [22] observed the same effect in the breathing system's HEPA filters used during anaesthesia, They hypothesise that the viruses, released from the droplet after contact with moisture accumulated on the filter, can be driven onwards by the flow of gas.…”
Section: Mask Discriminating Mouth and Nose (Mdmn)mentioning
confidence: 79%
“…They found that respiratory droplets could travel unexpected considerable distances depending on the high-speed wind conditions. Dbouk and Drikakis [19] also demonstrated that respiratory droplets from coughing or sneezing traveled a distance less than 2 m in the case of zero-wind conditions. Bourouiba [20] found that expelled respiratory droplets during human sneezing could travel up to 7-8 m at 36 km/h -108 km/h wind speeds.…”
Section: Introductionmentioning
confidence: 95%